Agricultural Waste and Residues 2018
DOI: 10.5772/intechopen.77008
|View full text |Cite
|
Sign up to set email alerts
|

Biochar and Animal Manure Impact on Soil, Crop Yield and Quality

Abstract: Four low-cost organic soil amendments (chicken manure, CM; horse manure, HM; yard water, YW; and sewage sludge, SS) that are generated daily in large amounts, and native bare soil were planted with tomato (Solanum lycopersicum var. Mountain spring) seedlings of 52 days old in raised black plastic-mulch. Each of the 5 treatments was also mixed with biochar to make a total of 10 treatments in a randomized complete block design (RCBD). Results revealed that total fresh weight of tomato fruits collected after thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 61 publications
2
9
0
2
Order By: Relevance
“…The use of bioindicators, such as soil enzymes activity, as monitoring tools to assess soil health and potential impact of SA, have been recommended [1,2]. Soil enzymes are very sensitive to the environmental stress caused by high levels of trace metals [3,4], hormones, and antibiotics [5] in animal manures, due to their impacts on soil biological activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of bioindicators, such as soil enzymes activity, as monitoring tools to assess soil health and potential impact of SA, have been recommended [1,2]. Soil enzymes are very sensitive to the environmental stress caused by high levels of trace metals [3,4], hormones, and antibiotics [5] in animal manures, due to their impacts on soil biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…Studies also have indicated that biochar (product of a process known as pyrolysis) used as a soil amendment could increase plant nutrients, soil cation exchange capacity (CEC), soil organic matter, soil microbial activities, and nutrient availability [1,23]. Biochar application to agricultural soils has a potential for climate change mitigation and improvement of soil properties, due to its increase of CEC, nutrient and water retention, and positive influences on soil microbial communities and crop yields [24].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Mierzwa-Hersztek et al [45] reported a positive correlation between microbial population and soil pH. Mixing SS amended soil with lime (calcium carbonate) or biochar (a carbon-rich product obtained when biomass, such as wood, manure, or leaves, is heated in a closed container) has been proposed to reduce soil contamination by trace metals due to their impact soil pH [46,47]. In addition, biochar is effective at retaining water-soluble nutrients required for many beneficial soil microorganisms [48].…”
Section: Resultsmentioning
confidence: 99%
“…Livestock manure provides a good source of essential nutrients for plants and is an excellent agent for improving soil quality and productivity. Although manure is the second largest source of GHG emissions in the agricultural sector [45], this amount of cattle manure application in the study had a benefit to soil improvement rather than an environmental impact. Shahzad et al [46] reported that the capacity of carbon sequestration by cattle manure application was 1-1.2 Mg h −1 higher than chemical fertilizer application [46].…”
Section: Interpretation Of Lcamentioning
confidence: 91%